Solitary Pulmonary Nodule: A Diagnostic Dilemma - Pardeep Masuta; Ioana Amzuta (Case Reports in Pulmonology)
This case describes a woman with a history of tobacco abuse who presented with a dry cough and was found to have an enlarging, 4 cm right upper lobe nodule without lymphadenopathy on CT imaging of the chest. Initial biopsies of the nodule suggested follicular lymphoma, but after obtaining more tissue, the pathology was negative for malignancy and instead showed necrotizing pneumonia. She proceeded to have negative infectious serology and cultures. She had negative rheumatological testing including MPO ANCA, PR-3 ANCA, and rheumatoid factor. She did not have renal failure, hemoptysis, weight loss, arthralgia, or upper airway inflammation. She ultimately underwent a right upper lobectomy, as the nodule was enlarging on repeat imaging. The pathology of the lung showed necrotizing granulomas with giant cells and fibrosis, but lacked active vasculitis or palisading histiocytes, further obscuring the diagnosis. She was conservatively managed with intranasal steroids, cough suppressants and antihistamines given her lack of severe symptoms. The diagnosis was most consistent with granulomatosis with polyangiitis (GPA) presenting as a solitary pulmonary nodule with pathology reflecting a mild degree of disease activity. The patient may manifest further signs of the disease while being monitored clinically.